الملكية القانونية والملكية النفعية وتطبيقهما في صكوك الإجارة: دراسة فقهية تقويمية مقارنة - فتاح، أبو بكر توفيق (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study examines one of the most important contemporary issues, which creates wide argument, in the field of Islamic economy, finance, industry and even among decision makers. This issue is the distinction between the legal (full) and beneficial (incomplete) property ownerships and the Sukuk holders' rights. The study focuses on evidences of those who support the idea and their references, adaptations and analogical deductions. It also discusses the most important implications of maintaining distinction between legal ownership and beneficial ownership or not maintaining it at all. Legal ownership as well as beneficial ownership have their own conditions. The research also touches on reasons of legal ownership. Moreover, it mentions the most important types of the Sukuk investment in Islamic jurisprudence generally, and types and provisions of the Sukuk al-Ijarah particularly. In addition, it discusses their applications in countries like Jordan, Saudi Arabia and Malaysia. Each of these models has its own problems. Therefore, the researcher discusses and provides the most distinctive solutions to all those problems. The researcher follows the inductive methodological approach, to extrapolate evidences and to look into the texts, adaptations and analogical detractions, and to give excellent examples, distinctive suggestions and alternative solutions for the problems. It also adopts the comparative approach to compare between the views of classical and modern Islamic jurists. The researcher has reached to important findings. Some of them are: the applications of legal ownership and ownership of utility in the Sukuk al-Ijarah are still at their early stages and have not taken the final shape in terms of their jurisprudential and legal origination; three experiments–although they are considered to be pioneers compared to others–are not free from problems; the legal solutions for them are possible as the researcher has proven in this thesis; and those who want to trace the effects of these applications should not forget those problems, to avoid repeating the same mistakes. Based on the above, it may be noted that this thesis is considered to be an addition to knowledge, and not just a repetition, or “copy” and “paste.”